Impacts of Climate change on soil microbial diversity, distribution and abundance - Amante, Guta; Wedajo, Mulisa (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Climate change, driven by anthropogenic activities, has far-reaching consequences for our planet. Among its many impacts, changes in temperature, elevated carbon dioxide levels, and shifts in greenhouse gas concentrations significantly affect soil ecosystems. In particular, soil microbial communities play a pivotal role in nutrient cycling, organic matter decomposition, and overall soil health. Soil microbial communities respond differently to the effects of climate change, like elevated warming and precipitation. The change in climatic conditions is reported to be adversely affecting soil biological activity directly through either drying or wetting of soil or affecting their associated plants. This review delves into the intricate relationship between climate change and soil microbial abundance, diversity, and distribution. The paper also discusses climatic change pressure on soil enzymatic activity and microbial biomasses, as well as soil faunal activity, as they are key indicators of soil health in a changing climate. Soil microbial communities cope with climate change by changing their diversity and physiological characteristics and by changing their symbiotic plants, which indicates the role of soil microbes in withstanding the negative impact of climate change.